2007
DOI: 10.1111/j.1365-2745.2007.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Evenness drives consistent diversity effects in intensive grassland systems across 28 European sites

Abstract: Summary1 Ecological and agronomic research suggests that increased crop diversity in speciespoor intensive systems may improve their provision of ecosystem services. Such general predictions can have critical importance for worldwide food production and agricultural practice but are largely untested at higher levels of diversity. 2 We propose new methodology for the design and analysis of experiments to quantify diversity-function relationships. Our methodology can quantify the relative strength of inter-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
362
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(393 citation statements)
references
References 41 publications
(51 reference statements)
23
362
5
3
Order By: Relevance
“…Recent studies have shown that both species richness and evenness have positive effects on the diversity-productivity relationship in ecosystems [59][60][61]. In accordance with another recent study [35], our measure of optical diversity showed a better correlation with the Shannon index than richness per se, suggesting that vegetation evenness (or heterogeneity) influences both optical diversity and the productivity patterns detected by NDVI.…”
Section: Biodiversity-ecosystem Functionsupporting
confidence: 76%
“…Recent studies have shown that both species richness and evenness have positive effects on the diversity-productivity relationship in ecosystems [59][60][61]. In accordance with another recent study [35], our measure of optical diversity showed a better correlation with the Shannon index than richness per se, suggesting that vegetation evenness (or heterogeneity) influences both optical diversity and the productivity patterns detected by NDVI.…”
Section: Biodiversity-ecosystem Functionsupporting
confidence: 76%
“…Increasing herbage yields with increasing plant species richness (positive plant diversity effects) were also shown in other studies on agricultural grassland mixtures (Frankow-Lindberg et al 2009;Kirwan et al 2007;Nyfeler et al 2009;Picasso et al 2008). The same was not the case for lucerne in pure stand, but growth conditions must have been optimal for lucerne, as herbage yields were high in both years and the proportion of lucerne in the mixture increased from the first to the second year.…”
Section: Discussionmentioning
confidence: 58%
“…Positive plant diversity-productivity relationships have been reported for experimental semi-natural grasslands (Cardinale et al 2006;Hector et al 1999;Tilman et al 1996) as well as temporary agricultural grasslands (Frankow-Lindberg et al 2009;Kirwan et al 2007;Nyfeler et al 2009;Picasso et al 2008). Generally, these relationships are explained, on the one hand, by niche differentiation and facilitation (Hector et al 2002;Tilman et al 2002) and, on the other hand, by greater probability of including a highly productive plant species in high diversity plots (Huston 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Tilman et al, 2006) and intensively managed grasslands across Europe (e.g. Kirwan et al, 2007), and thus applies to many different species compositions, environmental settings and management intensities. Increasing yields with increasing species diversity are typically explained by the niche complementarity concept (see section 2 for details).…”
Section: Discussionmentioning
confidence: 99%